Collaboration of Islamic Values and Local Wisdom in Communal Economic - Umah, Khurul Aimmatul; Sa'idaturrohmah, Nur (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The collaboration between Islamic values and local wisdom in communal economic management has the potential to create strong synergy in improving welfare and maintaining social harmony. This study aims to analyze this collaboration within the context of the multicultural society in Balun Village, Turi, Lamongan, known as the